History of cone beam computed tomography (CBCT) - Ghazali, Ahmad Badruddin (2023)
Cone Beam Computed Tomography (CBCT) can be regarded as a revolutionary technology in dental imaging. It has many applications in dentistry including endodontics, implant dentistry, orthodontics, oral and maxillofacial surgery, pathology, and TMJ imaging. Previously, three-dimensional, multiplanar imaging can be achieved by using the hospital-based computed tomography (CT) machine. Before we move on to the technical and interpretation of CBCT images, let’s have a look at the history of this technology.